ZISWAF Literation: Fundamental Strategies in Enhancing Zakah and Waqf Realization - Sari, Rizma Novita; Wijanarko, Zhafarina Shabhati; Pimada, Laila Masruro (International Journal of Zakat, 2023)
Zakah is an important instrument in life because it not only sees the side of divine worship but also has a close relationship with social and economic values. Zakah can be an alternative to eradicate poverty by helping each other in need in the form of infaq, shadaqah and waqaf. Thus, the large number of Muslims in Indonesia is also a sign that the potential for ZISWAF to be collected in Indonesia is also very large. However, the realization of the collection and distribution of Zakah, Infak, Shadaqah and Wakaf (ZISWAF) funds in Indonesia is still relatively low compared to its potential. One of the factors influencing the low level of public literacy regarding Zakah and Waqf. The purpose of this research is to identify and provide input in the form of strategies that can be implemented to increase Zakah and Waqf literacy in society. This study uses a qualitative approach combined with literature study methods. The results of this study were found in 20 scientific journals consisting of a Strategy for Increasing Content or Promotion and Dissemination of Sustainable Zakah and Waqf, Strategies for Conducting Zakah and Waqf Education for Young Generation in Families and Education, Strategies for Collaborating Zakah and Waqf Institutions with E- commerce and Strategy to Strengthen Zakah and Waqf institutions in Indonesia. With the strategy of increasing Zakah and Waqf literacy, it is hoped that the government can implement this strategy so that Zakah and Waqf literacy in society increases and the acquisition of Zakah and waqf funds also increases. Thus, the collection and management of Zakah and waqf can be more optimal and achieve the expected potential.